THE CASE OF INDONESIAN CONSUMER-GOODS INDUSTRIES: THE RELEVANCE OF INTELLECTUAL RESOURCES IN AFFECTING STOCK PRICES - Resi Ariyasa Qadri; Wafa Zhafira; Mierza Darsya Putra (JRAK, 2022)
This paper is aimed to investigate the linkage between the internal intellectual resources and firm share prices in the consumer goods sector in Indonesia. The purposive sampling is applied to form the sample data of 96 firms-years of the consumer-goods firms. We analyze the data by implementing the panel regression and bootstrap procedures. Our study finds that investors give positive appreciation towards the value-added human capital and the structural capital. A positive causality between the independent commissioner and the market price of equity is also confirmed. Our study contributes to supporting the resource-based view theory and offers a viewpoint on corporate value factors that investors should consider when making investments.